PERILAKU IBU TERHADAP KELENGKAPAN PEMBERIAN IMUNISASI DASAR PADA BAYI MASA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS SIALANG BUAH KABUPATEN SERDANG BEDAGAI TAHUN 2022 - Jamaliyah Jamaliyah; Ninsah Mandala Putri Br Sembiring (Jurnal Medika Husada, 2022)
The COVID-19 pandemic has disrupted health services around the world, including immunization services. Immunization is an effort to actively induce or increase a person's immunity against a disease, so that if one day they are exposed to the disease they will not get sick or only experience a mild illness. This study aims to determine the analysis of maternal behavior towards the completeness of basic immunization during the Covid-19 pandemic in the working area of ​​the Sialang Buah Health Center, Serdang Bedagai Regency in 2022. This type of research is an analytical survey with a cross sectional method approach. The number of samples used was 97 people. The data analysis technique uses the Chi Square test. the results obtained from 97 respondents, it was found that the administration of basic immunization did not decrease during the COVID-19 pandemic.